PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP HARGA SAHAM - maharani, destin alfianika; Sundari, Tri; Wirawan, Nugroho Budi (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2024)
ABSTRAC The stock price is the price that occurs on the stock market whose information is needed by investors in making decisions when investing in a company. Stock prices can be influenced by several factors, one of which was during the Covid-19 pandemic the combined stock price index fell to 4,905 or weakened 16.75% (Wicaksono, 2020). This study aims to determine the effect of profitability ratios proxied using earnings per share, liquidity proxied using the current ratio, and solvency proxied using the debt to equity ratio on stock prices in food and beverage manufacturing companies in 2018 – 2021. This research This study uses secondary data obtained from the Indonesia Stock Exchange for the period 2018 – 2021. The total sample used in this study was 47 samples, using a purposive sampling technique. This study uses multiple linear regression analysis. The results of this study indicate that partially the earnings per share, current ratio, and debt to equity ratio variables have no effect on stock prices. The results of this study indicate that simultaneously all variables of earnings per share, current ratio and debt to equity ratio have no effect on stock price variables.